A hybrid functional calculation of Tm3+ defects in germanium (Ge). (1st March 2016) - Igumbor, E.; Meyer, W.E.
Abstract: In this work, we present ab-initio calculation results for the Tm 3+ interstitial ( Tm i 3 + ), vacancy–interstitial complex (V Ge -Tm i 3+ ) and substitutional ( Tm Ge 3 + ) defects in germanium (Ge) as determined by the density functional theory (DFT) using the Heyd, Scuseria, and Ernzerhof (HSE06) hybrid functional. We calculated the formation energies and the charge state transition levels of different configurations. Our results show that the Tm 3+ interstitial exists in the hexagonal configuration with low formation energy. The formation energies for V Ge − Tm i 3 + and Tm Ge 3 + were as low as 0.84 eV. The most energetically favourable defects were the V Ge − Tm i 3 + in the axial configuration and the Tm Ge 3 + . The Tm Ge 3 + and V Ge − Tm i 3 + introduced a single acceptor ϵ ( 0 / − 1 ) charge state transition level that was positioned deep in the middle of the band gap. The majority of the levels induced by the defects under investigation, were either shallow donor or acceptor level lying close to the band gap edges.